Development of “Alat Bantu Pengambilan Keputusan ber-KB” Application - Erni Dwi Widyana; Ari Kusmiwiyati (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2022)
Women of childbearing age are very vulnerable to having difficulty in determining a proper contraceptive method due to poor knowledge about the safety of these contraceptive methods. Counseling with Decision-Making Aids is an important thing in the provision of family planning services. WHO has developed Decision-Making Tool as a manual family planning decision aid which was adapted by BKKBN and STARH as “Alat Bantu Pengambilan Keputusan ber-KB”. Such tool is made in the form of a booklet with two sides which is still rarely used by midwives when conducting family planning counseling. This study aims to analyze the results of trial on application-based